Teaching and learning physics using technology: Making a case for the affective domain. Issue 2 (3rd April 2018) - Ramma, Yashwantrao; Bholoa, Ajeevsing; Watts, Mike; Nadal, Pascal Sylvain
ABSTRACT: Even though its importance is underscored in many research pursuits, attention to the affective domain in learning is often neglected at the expense of the cognitive development of students studying science, in particular physics. In this paper we propose a framework, the pedagogical technological integrated medium (PTIM) founded on the TPACK model, that builds on the existing premises of pedagogy, content and technology to make space for the affective domain where these three premises intersect with each other. We operationalize the PTIM framework through a multi-loop model that explores the affective dimension as an overarching space for interaction among learners, teachers and parents through a series of stages encompassing home tasks, as well as classroom and out-of-school activities. Within the qualitative paradigm, we substantiate from two case studies, an exploratory and an evaluative one in two different schools, that a succinct synchronisation of these various interactive elements promotes knowledge construction springing from the affective domain in terms of motivation, interest and values and also from their inter-relationships.